Impact of Urban Surface Roughness Length Parameterization Scheme on Urban Atmospheric Environment Simulation - Meichun Cao; Zhaohui Lin (Journal of Applied Mathematics)
In this paper, the impact of urban surface roughness length z0 parameterization scheme on the atmospheric environment simulation over Beijing has been investigated through two sets of numerical experiments using the Weather Research and Forecasting model coupled with the Urban Canopy Model. For the control experiment (CTL), the urban surface z0 parameterization scheme used in UCM is the model default one. For another experiment (EXP), a newly developed urban surface z0 parameterization scheme is adopted, which takes into account the comprehensive effects of urban morphology. The comparison of the two sets of simulation results shows that all the roughness parameters computed from the EXP run are larger than those in the CTL run. The increased roughness parameters in the EXP run result in strengthened drag and blocking effects exerted by buildings, which lead to enhanced friction velocity, weakened wind speed in daytime, and boosted turbulent kinetic energy after sunset. Thermal variables (sensible heat flux and temperature) are much less sensitive to z0 variations. In contrast with the CTL run, the EXP run reasonably simulates the observed nocturnal low-level jet. Besides, the EXP run-simulated land surface-atmosphere momentum and heat exchanges are also in better agreement with the observation.